Near infrared transillumination compared with radiography to detect and monitor proximal caries: A clinical retrospective study. (March 2018) - Abdelaziz, Marwa; Krejci, Ivo; Perneger, Thomas; Feilzer, Albert; Vazquez, Lydia
Abstract: Objective: To compare near infrared transillumination device, DIAGNOcam (DC) and bitewing radiography (BW) for the detection of proximal caries. Materials and methods: This retrospective analysis of DC and BW images of 18 students in dental medicine who had consented to the anonymous use of their dental record. The data included BW and DC images performed for a check-up in 2013, and corresponding follow-up images performed in 2015. Two observers rated 376 proximal surfaces on a 4-level dentin lesion scale and reached a unanimous rating for each surface. Calculated measures of agreement for each assessment method over time provided the reproducibility of the information obtained by each method. Results: Agreement between 2013 and 2015 within each method was excellent (intraclass correlation coefficient, BW: 0.86, DC: 0.90). Agreement between DC and BW was similar for dentin lesion detection, but was low for enamel caries detection; DC detected more enamel caries than BW. Agreement between DC and BW was modest (0.33 in 2013 and 0.36 in 2015), chiefly because DC identified more enamel caries. Conclusion: This study shows that DC is as reliable as BW to detect proximal dentin lesions. DC detects proximal enamel lesions at an earlier stage than BW. DC enables clinicians to differentiate lesions limited to the enamel from lesions that have reached the enamel dentin junction. Regular monitoring with DC should help provide individualized preventive measures and early non-invasive caries management. Clinical significance: The early detection of enamel lesions with near infrared transillumination can help clinicians undertake early non invasive treatments to prevent or slow down the progression of initial proximal lesions.